2017
DOI: 10.1007/s11256-017-0406-0
|View full text |Cite|
|
Sign up to set email alerts
|

A Social Constructivist Approach to Preparing School Counselors to Work Effectively in Urban Schools

Abstract: A social constructivist approach to preparing school counselors to work effectively in urban schools. Urban Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As a result of individual, interpersonal, and institutional challenges, school counselors emphasized the importance of creating a safe and positive environment where Latinx adolescents felt comfortable to share their stories. To set up healthy therapeutic relationships, counselors can use cuento therapy or dichos , which are two culture‐centered interventions (Comas‐Diaz, 2017; Martinez, Dye, & Gonzalez, 2017), to connect and confirm Latinx adolescents’ shared cultural and social experiences. Counselors also can use active listening with paraphrases of reflection and meaning to confirm Latinx adolescents’ experiences and stories (Gladding, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of individual, interpersonal, and institutional challenges, school counselors emphasized the importance of creating a safe and positive environment where Latinx adolescents felt comfortable to share their stories. To set up healthy therapeutic relationships, counselors can use cuento therapy or dichos , which are two culture‐centered interventions (Comas‐Diaz, 2017; Martinez, Dye, & Gonzalez, 2017), to connect and confirm Latinx adolescents’ shared cultural and social experiences. Counselors also can use active listening with paraphrases of reflection and meaning to confirm Latinx adolescents’ experiences and stories (Gladding, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that first-generation students are at a significant disadvantage for attending and completing postsecondary education (Choy, 2001;Engle, 2007;R. R. Martinez, Baker, & Young, 2017;R. R. Martinez, Dye, & Gonzalez, 2017).…”
Section: First-generation Statusmentioning
confidence: 99%
“…In some cases, the parents of first‐generation Latinx students may have completed some coursework, but these students will be the first in their immediate family to graduate with a postsecondary degree/credential. Researchers have found that first‐generation students are at a significant disadvantage for attending and completing postsecondary education (Choy, 2001; Engle, 2007; R. R. Martinez, Baker, & Young, 2017; R. R. Martinez, Dye, & Gonzalez, 2017). First‐generation students are more likely to be Latinx, as well as to come from lower socioeconomic groups than their counterparts, which previous researchers have found decreases the probability of these students attending and completing postsecondary education (Choy, 2001; Engle, 2007).…”
Section: Understanding Latinx College Readiness Culturementioning
confidence: 99%
“…Whereas the literature on the CCR needs of African American females, in particular, is limited ; these statistics suggest that this population may not be receiving equitable opportunities to succeed academically or explore postsecondary options. The K-12 school structure is one that views students of color through a deficit lens and does not encourage the mind-sets and behaviors that can lead to college and career aspirations (Martinez, Dye, & Gonzalez, 2017). Moreover, the collectivistic cultural viewpoint of African Americans may influence these females to consider familial elements into postsecondary planning (Maxwell, 2007), such as making the decision to stay close to home to care for parents or younger siblings.…”
Section: Strengths and Considerations Of African American Femalesmentioning
confidence: 99%